Algebra operatorów gładkich - Ciaś, Tomasz (My University, 2014)
Celem rozprawy jest zbadanie własności nieprzemiennej algebry Frécheta z inwolucją, zwanej algebrą operatorów gładkich. Algebra ta jest izomorficzna jako przestrzeń Frécheta z przemienną algebrą s ciągów szybko malejących do zera (izomorficzną także z dobrze znaną przestrzenią Schwartza gładkich funkcji szybko malejących) i w ten sposób jest pewnego rodzaju nieprzemiennym odpowiednikiem algebry s. Znaczna część rozprawy jest poświęcona opisie i klasyfikacji domkniętych przemiennych *-podalgebr algebry operatorów gładkich. Na przykład, pokazujemy, że taka podalgebra jest izomorficzna z domkniętą *-podalgebrą algebry s wtedy, i tylko wtedy, gdy jest izomorficzna (jako przestrzeń Frécheta) z pewną dopełnialną podprzestrzenią s. Ponadto znajdujemy algebrę multiplikatorów algebry operatorów gładkich, dowodzimy twierdzeń o reprezentacji spektralnej i reprezentacji Schmidta elementów tej algebry oraz pokazujemy, że istnieje hölderowsko ciągły rachunek funkcyjny dla gładkich operatorów normalnych. Większość dowodów jest oparta na teorii ograniczonych i nieograniczonych operatorów na przestrzeni Hilberta oraz teorii nuklearnych przestrzeni Frécheta.

The aim of this dissertation is to investigate the properties of the noncommutative Fréchet algebra with involution, called the algebra of smooth operators. This algebra is isomorphic as a Fréchet space to the commutative algebra s of rapidly decreasing sequences (isomorphic also to the well-known Schwartz space of smooth rapidly decreasing functions), and thus it is a kind of noncommutative analogue of the algebra s. A significant part of the dissertation is devoted to the description and classification of the closed commutative *-subalgebras of the algebra of smooth operators. For instance, we show that such a subalgebra is isomorphic to a closed *-subalgebra of the algebra s if and only if it is isomorphic (as a Fréchet space) to a complemented subspace of s. We also find the multiplier algebra of the algebra of smooth operators, prove theorems on spectral and Schmidt representations of elements of this algebra and show that there is a Hölder continuous functional calculus for normal smooth operators. Most of the proofs are based on the theory of bounded and unbounded operators on a Hilbert space and the theory of nuclear Fréchet spaces.
Algebra of smooth operators
Wydział Matematyki i Informatyki
Keywords: gładkie operatory zwarte; smooth compact operators; algebry topologiczne z inwolucją; topological algebras with involution; nuklearne przestrzenie Frecheta; nuclear Frechet spaces; C*-algebry; C*-algebras